W-band S–Z relationships for rimed snow particles: observational evidence from combined airborne and ground-based observations - S. Fuller; S. A. Marlow; S. Haimov; M. Burkhart; K. Shaffer; A. Morgan; J. R. Snider (Atmospheric Measurement Techniques, 2023)
Values of undercatch-corrected liquid-equivalent snowfall rate (S) at a ground site and microwave reflectivity (Z) retrieved using an airborne W-band radar were acquired during overflights. The temperature at the ground site was between −6 and −15 ∘C. At flight level, within clouds containing ice and supercooled liquid water, the temperature was approximately 7 ∘C colder. Additionally, airborne measurements of snow particle imagery were acquired. The images demonstrate that most of the snow particles were rimed, at least at flight level. A relatively small set of S–Z pairs (four) is available from the overflights. Important distinctions between these measurements and those of Pokharel and Vali (2011), who reported S–Z pairs and an S–Z relationship for rimed snow particles, are (1) the fewer S–Z pairs, (2) the method used to acquire S, and (3) the altitude, relative to ground, of the W-band Z retrievals. This analysis corroborates the fact that the S–Z relationship reported in Pokharel and Vali (2011) yields an S – in scenarios with snowfall produced by riming – substantially larger than that derived using an S–Z relationship developed for unrimed snow particles.